Use of lapillus otolith microchemistry as an indicator of the habitat of Genidens barbus from different estuarine environments in the southwestern Atlantic Ocean - Avigliano, Esteban (2015)
The marine catfish Genidens barbus is an anadromous species from South America. The aim of the present study was to evaluate the use of lapillus otolith microchemistry (Sr:Ca; Ba:Ca and Mg:Ca ratios) as an indicator of changes in habitat use and identify the potential breeding areas and fish stocks of G. barbus populations from the Plata Basin (Paraná River Delta and De la Plata River estuary-Argentina) and Lagoa dos Patos coastal lagoon (southern Brazil). Sr:Ca, Ba:Ca and Mg:Ca ratios were measured in the core area (inner 4 rings) and external area (outer 3–4 rings) of the otoliths by ICP-OES. The Sr:Ca ratio tended to be higher in the otolith external area than in the core area, while the Ba:Ca ratio followed the opposite pattern. This suggests the displacement of fish toward higher salinity areas. The Sr:Ca, Ba:Ca, Mg:Ca ratios in the core and external areas of the otoliths from the Plata Basin differed significantly from those of the otoliths from Lagoa dos Patos. This may indicate the occurrence of two different breeding sites and at least two fish stocks in the study region.